Computer Aided Modelling of Human Pelvic Bone - John, A.; Orantek, P. (Engineering Transactions, 2003)
Numerical modelling of human pelvic bone makes it possible to determine the stress and strain distribution in bone tissue. Before numerical analysis, the geometrical model of analyzed structure should be prepared. It is an important step in numerical analysis because the obtained results depend on it. Up to the present, in the most of examples, the creation of geometrical model was done in a simple but time-consuming way. In the paper the numerical routine, translating data from the coordinate measuring machine to the Patran code is presented. At the first step, the geometrical model with the layer structure of bone tissue is created. The geometrical data is the basis to create an FE mesh. After meshing, the boundary conditions and load should be assumed. When the load and boundary conditions are known, the strain and stress distribution can be calculated using the Nastran or Advanced FEA code. The presented program enables to reduce the time of creation of numerical model.